Trend-Driven Innovation for RTE Food Market: A Comparison Study Between Consumers from Malaysia and Indonesia - Ahmat, Nur Hidayah Che; Ismail, Wan Rusni Wan; Ramli, Rafidah Aida; Handajani, Sri; Ngelambong, Anderson (Information Management and Business Review, 2024)
The ready-to-eat (RTE) food market is growing worldwide. Nevertheless, a limited study was found where researchers compare consumer behavioral intention toward RTE foods between countries. This study compares consumers in Malaysia and Indonesia regarding their food preferences and behavioral intentions toward RTE foods. Using a quantitative cross-sectional approach, the researchers developed an online survey and distributed the survey link to consumers aged 18 years and above from both countries via social media platforms. The dataset comprised 321 responses from Malaysia and 262 from Indonesia. Based on the analyses, findings reported some similarities and differences in consumer preferences and behavior intention between both countries. The highest percentages of Malaysian respondents were recorded for plant-based, genetically modified, gluten-free, and allergen-free foods. Interestingly, the highest percentage of Indonesian respondents reported for insect-based food than the Malaysians. More Malaysian consumers preferred ethnic foods from different cultures than Indonesians. About the same highest percentages of consumers from both countries preferred cell-cultured meat, 3D printed foods, and vegan foods. For Malaysian samples, attitude and subjective norms significantly influenced their behavior intention toward RTE foods. For Indonesian samples, subjective norms and behavioral control significantly influence consumer behavior intention toward RTE foods. Findings are relevant for food producers and marketers to explore the young consumer market and to identify new products to fulfill the market demand. This study broadens and deepens the current understanding of both countries’ RTE food trends and consumer behavioral patterns. Food producers should promote RTE food products by highlighting their benefits through marketing channels.